Discovering multifaceted role of vanillic acid beyond flavours: Nutraceutical and therapeutic potential. (April 2022) - Kaur, Jaskiran; Gulati, Monica; Singh, Sachin Kumar; Kuppusamy, Gowthamarajan; Kapoor, Bhupinder; Mishra, Vijay; Gupta, Saurabh; Arshad, Mohammed F.; Porwal, Omji; Jha, Niraj Kumar; Chaitanya, M.V.N.L.; Chellappan, Dinesh Kumar; et al.
Abstract: Background: Vanillic acid is a phenolic compound, found in various dietary sources and medicinal plants. Apart from its extraction from these biological sources, it is also synthesized chemically. It is used as flavouring agent in various food products. It possesses anticancer, antiobesity, antidiabetic, antibacterial, anti-inflammatory, and antioxidant effects. Despite possessing good therapeutic potential and safety profile, it has not been well explored as nutraceutical or, therapeutic moiety. Scope and approach: Literature search was conducted to systematically review the various mechanistic pathways through which vanillic acid showed multiple therapeutic effects. Along with these pathways, other applications of vanillic acid and its derivatives are highlighted. Some of the patents that have been filed hitherto, for the production and uses of vanillic acid are also entailed in the manuscript. Key findings and conclusion: Vanillic acid exerts diverse bioactivity against cancer, diabetes, obesity, neurodegenerative, cardiovascular, and hepatic diseases by inhibition of the associated molecular pathways. Its derivatives also possess the therapeutic potential to treat autoimmune diseases as well as fungal and bacterial infections. Owing to these benefits, vanillic acid has great potential to be used as a nutraceutical and provides scope for therapeutic uses beyond its traditional use as a flavouring agent. However, its oral bioavailability is limited due to its rapid elimination (metabolism) from the plasma. This, in turn, impedes its successful delivery through conventional formulations. Hence, efforts are required to develop nanoformulations of vanillic acid to overcome the associated challenges. Highlights: Vanillic acid is used as flavouring agent that can be synthesized and extracted from natural sources. The roots of Angelica sinensis are the largest commercial natural source of vanillic acid. It is used as powerful antioxidant in food products and drinks. Therapeutic benefits of vanillic acid are mostly due to modulation of Nrf 2 and NF-ĸB pathway. Patents filed on nutraceutical applications of vanillic acid indicate its commercial potential.